THE INFLUENCE OF TECHNOOGY ON PARENT RESPONSIVENESS - Rausch, Robyn; Dykes-Harrell, Lisa (Acta Scientiae et Intellectus, 2024)
Objective. Technology in the homes has been increasing in the new millennium, and has changed how parents and children interact. The goal of this study was to explore whether parents use technology in responsive ways that support childhood development or unresponsive ways that disrupt the parent-child relationship. Design. This study used a likert scale survey to ask 40 parents (ages 24-42) how they use technology with their children (ages 3-8). Results. Parents use technology in both responsive and unresponsive ways; however, parents appear to use technology more often to be responsive rather than to disrupt the relationship. Conclusions. Parents appear to use technology responsively with their children more often than unresponsively. These findings contrast modern media and the single previously published study that was found. These results provide guidance for encouraging the use of technology by parents to support child development.